2019
DOI: 10.1103/physreva.100.062329
|View full text |Cite
|
Sign up to set email alerts
|

Cut-resistant links and multipartite entanglement resistant to particle loss

Abstract: In this work, we explore the space of quantum states composed of N particles. To investigate the entanglement resistant to particles loss, we introduce the notion of m-resistant states. A quantum state is m-resistant if it remains entangled after losing an arbitrary subset of m particles, but becomes separable after losing a number of particles larger than m. We establish an analogy to the problem of designing a topological link consisting of N rings such that, after cutting any (m + 1) of them, the remaining … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
10
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 50 publications
0
10
0
Order By: Relevance
“…Interestingly, it turns out that the Borromean states emerging in our model need to exhibit Greenberger-Horne-Zeilinger (GHZ) [16] type of entanglement between the internal degrees of freedom of the particles. Such entanglement is genuinely multipartite and is very sensitive to particle losses, which can be considered a Borromean property [17,18]. This showcases an intuitive link between the properties of particles' correlations and their dynamics.…”
Section: Introductionmentioning
confidence: 88%
“…Interestingly, it turns out that the Borromean states emerging in our model need to exhibit Greenberger-Horne-Zeilinger (GHZ) [16] type of entanglement between the internal degrees of freedom of the particles. Such entanglement is genuinely multipartite and is very sensitive to particle losses, which can be considered a Borromean property [17,18]. This showcases an intuitive link between the properties of particles' correlations and their dynamics.…”
Section: Introductionmentioning
confidence: 88%
“…The output state is given by ρ out = E S (ρ in ) with ρ in the input state. It is marvelous that some quantum states like Dicke the states keep entangled after passing through the particle-lose channel [16][17][18][19]. This inspires a natural problem of characterizing the multipartite quantum systems in term of particle-lose channels.…”
Section: Introductionmentioning
confidence: 99%
“…party-lose noises in which all the local particles shared by one party are taken as one unavailable high-dimensional particle or quantum sources. Different from the permutationally symmetric states [16][17][18][19], these entangled systems depend on network configurations, which gives rise to an interesting problem in characterizing distributed quantum resources for distributed quantum information processing.…”
Section: Introductionmentioning
confidence: 99%
“…It is indicated that many physical implementations of qubits, for example ion traps, optical lattices and linear optics, suffer from loss of qubits [3]. The entanglement resistant to particles loss via tracing out the particles was investigated [4].…”
Section: Introductionmentioning
confidence: 99%